Single-Advisor System or Joint Advisor System: The Preference and Satisfaction of PhD Students for Different Supervision Models. Issue 3 (4th May 2018) - Shen, Wenqin; Gao, Yao; Zhao, Shikui
Abstract: Data from a PhD quality survey and related interview materials are used to analyze the preferences of Chinese PhD students for different supervision methods, and the differences between disciplines of the satisfaction of PhD students under single-advisor model and joint supervision model toward their academic supervision are compared. The research results show that most PhD students, especially engineering PhD students, are generally inclined to choose a joint supervision model. However, there are no significant differences in the satisfaction toward the two supervision models with the exception of medical PhD students. Considering that in some disciplines even though some PhD students are under single-advisor supervision in name, they actually are under joint advisor supervision, the regression results may underestimate the actual results of the joint supervision. Furthermore, the study also found that if the supervision-model PhD students prefer matches the actual supervision model, their satisfaction is also higher. Looking at the education development trends for international graduate students and student expectations, China should further promote joint supervision systems and also maintaining the responsibilities of head advisors.